KESESUAIAN DESAIN ERGONOMIS BANGKU KULIAH BERDASARKAN DATA ANTROPOMETRI PADA MAHASISWA FAKULTAS KESEHATAN - Fitra Deny; Melya Susanti; Tati Khairina; M. Reyhan Daffa Abdullah; Muhammad Ivan (Nusantara Hasana Journal, 2024)
Background : Ergonomics can be interpreted as a science that regulating work procedures, work posture or work attitude, proper planning and prevention of work-related diseases such as low back pain and disorders. College chairs that are not ergonomic can make students feel uncomfortable so that will interfered their concentration during the learning process and can also cause pain in certain parts such as the back, back of the waist, upper neck, and can obstruct the health of the spine. Objective: To find out the compatibility of the ergonomics of lecture halls with the anthropometry of students class of 2019. Methods: This research field covers medical field, especially public health sciences. This research was conducted at the Faculty of health at a university in Padang City, in November-January 2022. This type of research was a numerical descriptive study with a cross sectional design. The total population is 146 people with 62 samples using simple random sampling technique. Univariate data analysis is presented in the form of a frequency distribution, and data processing uses a computerized SPSS program version of IBM 25.0 Results: Anthropometric data with an average elbow height of 20.97 cm, an average knee height of 45.97 cm, an average hip width of 26.06 cm and an average hip-popliteal length of 37.40 cm. The results of the 2019 Unbrah Faculty of Medicine college chairs measurements where the backrest height was 38 cm, the table height was 24 cm, the width of the chair base was 32 cm, the length of the chair base was 37 cm and all respondents namely 62 people (100%) did not have the compatibility ergonomics of a college chairs with anthropometry. Conclusion: The compatibility of the ergonomics of the college chairs with the anthropometry students class of 2019 is not suitable.